2012
DOI: 10.1038/bonekey.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of skeletal muscle strength and mass with relevance to sarcopenia

Abstract: Skeletal muscle is a highly heritable quantitative trait, with heritability estimates ranging 30 -85 % for muscle strength and 50 -80 % for lean mass. That strong genetic contribution indicates the possibility of using genetic information to individualize treatments for sarcopenia or even aid in prevention strategies through the use of genetic screening prior to the functional limitations. Though these possibilities provide the rationale for genetic studies of skeletal muscle traits, few genes have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 127 publications
2
28
0
2
Order By: Relevance
“…1). These findings concur with the published literature, suggesting that genetic variation has an influence on SM traits and that there may be different clinically meaningful thresholds of muscle mass for which function is impaired [25]. Based on our study, age, race, and gender are strong determinants of SM mass and must be accounted for when interventions are planned.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1). These findings concur with the published literature, suggesting that genetic variation has an influence on SM traits and that there may be different clinically meaningful thresholds of muscle mass for which function is impaired [25]. Based on our study, age, race, and gender are strong determinants of SM mass and must be accounted for when interventions are planned.…”
Section: Discussionsupporting
confidence: 91%
“…Second, muscle mass may not be representative of muscle strength and endurance. Last, genetics play an important role in the determination of muscle mass [25], as clearly demonstrated by differences in sex and race. We found that SM decreases with age and is higher in black males, followed by white males, black females, and white females, across all age groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in Table 1, there are positive and negative findings for some genetic markers but few of these polymorphisms have been replicated. Notably, for the TRHR gene variant, there is only one study supporting the link with lean body mass variation [6, 7] in 1000 US whites after several replication attempts in three different cohorts consisting of in total over 6000 white US and Chinese participants. The Vitamin D receptor BsmI (rs1544410) polymorphism has also been associated with muscle strength in elderly population in three studies but results remain inconclusive [8].…”
Section: Commentmentioning
confidence: 99%
“…50-80 %) und Muskelkraft (mit ca. 30-85 %) sind zu einem nicht unerheblichen Ausmaß genetisch determiniert [9]; die oben beschriebenen Prozesse betreffen unterschiedliche Individuen in unterschiedlichem Ausmaß.…”
Section: Altersassoziierte Faktorenunclassified